Touching upon the history of the Khotetovsky princes’ land ownership (in concern with the question of the location of the centre of Khotetovsky’s inherited land in Karachevsky Principality) - A. V. Deduk (Историко-географический журнал)
The Upper Oka region is noted for the fact that during 16th–17th centuries it still holds the remains of the land ownership by the descendants of the princes Obolensky, Mosalsky, Vorotynsky, Volkonsky, etc., who used to own lands in the indicated region. One of such family names might be the Khotetovsky family. The representatives of the Khotetovsky clan at least twice left for Moscow: for the first time in 1408 accompanied by Prince Svidrigailo, and for the second time around 1500 with Prince Semyon Belsky. The article analyzes the references to the Khotetovsky clan and their mentioning in the 16th–17th centuries, and reconstructs their genealogy. Different literary sources contain mutually exclusive views concerning the location of the centre of Khotetovsky’s lands. The undertaken study of cadastral and cartographic materials of the 16th–19th centuries enabled the author to find out five toponyms with the root -KHOTET- which might have to do with the centre of the Khotetovsky lands, namely village Yudina, Khotetovskoye of Karachevsky District, Khotetovo, Perkovo of Karachevsky District (after Catherine’s II reformation — Bolkhovsky District), settlement Khotetovo of Orlovsky District (after the administrative reform — Mtsensky District) and hamlet Khotetovsky, village Khotetovo of Aleksinsky District. The article also touches upon the land ownership of the Khotetovsky family in Vorotynsky District. Taking into account the deep analysis of clerical documents of the Domestic Prikaz — Patrimonial board a conclusion is drawn that the only ancestral ownership of the Khotetovsky Princes was settlement Khotetovo which also represents the centre of the Khotetovsky Princes’ lands.